Functional Analysis of Gene-Silencing Suppressors from Tomato Yellow Leaf Curl Disease Viruses - Pérez-Luna, Ana Isabel; Morilla, Gabriel; Voinnet, Olivier; Rodríguez-Bejarano, Eduardo (APS Publications, 2012)
Tomato yellow leaf curl disease (TYLCD) is caused by a complex of phylogenetically related Begomovirus spp. that produce similar symptoms when they infect tomato plants but have different host ranges. In this work, we have evaluated the gene-silencing-suppression activity of C2, C4, and V2 viral proteins isolated from the four main TYLCDcausing strains in Spain in Nicotiana benthamiana. We observed varying degrees of local silencing suppression for each viral protein tested, with V2 proteins from all four viruses exhibiting the strongest suppression activity. None of the suppressors were able to avoid the spread of the systemic silencing, although most produced a delay. In order to test the silencing-suppression activity of Tomato yellow leaf curl virus (TYLCV) and Tomato yellow leaf curl Sardinia virus (TYLCSV) proteins in a shared (tomato) and nonshared (bean) host, we established novel patch assays. Using these tools, we found that viral proteins from TYLCV were able to suppress silencing in both hosts, whereas TYLCSV proteins were only effective in tomato. This is the first time that viral suppressors from a complex of diseasecausing geminiviruses have been subject to a comprehensive analysis using two economically important crop hosts, as well as the established N. benthamiana plant model.
Keywords: Virus fitopatógenos; RNA-silencing; suppressor; geminivirus; C2/AC2; C4/AC4; V2/AV2